Benzodiazepines and Related Drugs as a Risk Factor in Alzheimer's Disease Dementia - Ettcheto, Miren; Olloquequi, Jordi; Sánchez-López, Elena; Busquets, Oriol; Cano, Amanda; Manzine, Patricia Regina; Beas-Zarate, Carlos; Castro-Torres, Rubén D.; García, Maria Luisa; Bulló, Mónica; Auladell, Carme; Folch, Jaume; et al. (Frontiers in Aging Neuroscience, 2020)
Benzodiazepines (BZDs) and Z-drugs are compounds widely prescribed in medical practice due to their anxiolytic, hypnotic and muscle relaxant properties. Yet, their chronic use is associated with cases of abuse, dependence and relapse in many patients. Furthermore, elderly people are susceptible to alterations in pharmacodynamics, pharmacokinetics, as well as to drug interaction due to polypharmacy. These situations increase the risk for the appearance of cognitive affectations and the development of pathologies like Alzheimer’s disease (AD). In the present work there is a summary of some clinical studies that have evaluated the effect of BZDs and Z-drugs in the adult population with and without AD, focusing on the relationship between their use and the loss of cognitive function. Additionally, there is an assessment of preclinical studies focused on finding molecular proof on the pathways by which these drugs could be involved in AD pathogenesis. Moreover, available data (1990-2019) on BZDs and Z-drugs use, among elderly patients, with and without AD was compiled in this work. Finally, the relationship between the use of BZD and Z-drugs for the treatment of insomnia and the appearance of AD biomarkers was analysed. Results pointed to a vicious circle that would worsen the condition of patients over time. Likewise, it put into relevance the need for close monitorization of those patients using BZDs that also suffer from AD. Consequently, future studies should focus on optimizing strategies for insomnia treatment in elderly by using other substances like melatonin agonists, described to have a much more significant safety profile.